PENGARUH PENATAAN PRODUK DAN SUASANA TOKO TERHADAP PEMBELIAN TIDAK TERENCANA PADA RIP CURL STORE SEMINYAK KUTA BADUNG - Sumerta, I Komang; Pranawa, I Made Baji; Indahyani, Desak Nyoman Tri; Redianingsih, Ni Komang (Buletin Studi Ekonomi; VOL.26.NO.1.FEBRUARI 2021, 2021)
The formulation of the problem in this study is how the simultaneous or partial influence between display product and store atmosphere on impulse buying at Rip Curl Store Seminyak Kuta Badung? The purpose of this study was to determine the effect of simultaneous and partial display product and store atmosphere on impulse buying at Rip Curl Store Seminyak Kuta Badung. The number of samples is determined by purposive random sampling technique, as many as 100 consumers at Rip Curl Store Seminyak Kuta Badung. Data were analyzed by classical assumption test, multiple linear regression analysis, determination analysis, simultaneous significance test (F-test) and partial significance test (t-test). The results showed that there was a positive and significant effect both partially and simultaneously between display product and store atmosphere on impulse buying at Rip Curl Store Seminyak Kuta Badung.